METHODS OF QUALITY ASSURANCE IN THE PERFORMANCE OF HIGHER EDUCATION INSTITUTIONS JORDANIAN "THEORETICAL STUDY" - AL-Momani, Mohammad Omar (Jurnal Pendidikan Sosiologi dan Humaniora, 2022)
The study aimed to identify the methods used by higher education institutions to achieve quality education Quality has received significant attention in most countries of the world as one of the thestrutsbasic for education systems that have to keep up with the changes Globalism Andadapt to it And the starting point for scientifically qualified human cadres to participate in achieving development in its various dimensions, and facing the adverse effects resulting from the drivers of change, leading to practical solutions that benefit societies. To achieve this, the quality assurance process works onApply advanced methods to improve higher education and activate existing practices. Development payout will pass and achieve the highest possible outcomes for higher education institutions to suit local, regional and global needs.